2016
DOI: 10.1017/s1366728916000651
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dilation is sensitive to the cognate status of words: further evidence for non-selectivity in bilingual lexical access

Abstract: The cognate facilitation effect (i.e., a processing advantage for cognates compared to non-cognates) is an evidence of language non-selectivity in bilingual lexical access. Several studies using behavioral or electrophysiological measures have demonstrated that this effect is modulated by the degree of formal overlap between translations. However, it has never been tested with a psychophysiological measure such as pupillometry. In the present study we replicate the cognate facilitation effect by examining reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…Research examining the task‐evoked pupillary response (TEPR) provides evidence that the relationship between pitch accenting and referent status affects comprehenders' cognitive load during spoken discourse processing. Generally, smaller pupillary responses are observed when language processing is facilitated by intrinsic characteristics of the linguistic input such as speech quality (Koch & Janse, 2016; Kuchinsky et al, 2013; McGarrigle, Dawes, Stewart, Kuchinsky, & Munro, 2017; Tamási, McKean, Gafos, Fritzsche, & Höhle, 2017; Wagner, Toffanin, & Başkent, 2016; Winn, Edwards, & Litovsky, 2015; Zekveld, Kramer, & Festen, 2010), lexical characteristics (Chapman & Hallowell, 2015; Frank & Thompson, 2012; Geller, Landrigan, & Mirman, 2019; Geller, Still, & Morris, 2016; Guasch, Ferre, & Haro, 2017; Haro, Guasch, Vallès, & Ferré, 2017; Hyönä, Tommola, & Alaja, 1995; Kuchinke, Võ, Hofmann, & Jacobs, 2007; Ledoux et al, 2016; Lõo, van Rij, Järvikivi, & Baayen, 2016; Papesh & Goldinger, 2012), lack of syntactic ambiguity (Ben‐Nun, 1986; Just & Carpenter, 1993; Nikuni, Yasunaga, Iwasaki, & Muramoto, 2015; Sauppe, 2017; Schluroff, 1982; Sevilla, Maldonado, & Shalóm, 2014), and discursive implications (Demberg & Sayeed, 2016; Tromp, Hagoort, & Meyer, 2016). Conversely, larger pupillary responses are observed when language must be comprehended while simultaneously performing other tasks (Causse, Peysakhovich, & Fabre, 2016; Demberg & Sayeed, 2016; Koelewijn, de Kluiver, Shinn‐Cunningham, Zekveld, & Kramer, 2015; Koelewijn, Shinn‐Cunningham, Zekveld, & Kramer, 2014; Kramer et al, 2013) as well when language comprehension is difficult due to conditions such as aphasia and cognitive aging (Chapman & Hallowell, 2015; Hochmann & Papeo, 2014; Koch & Janse, 2016; Piquado, Isaacowitz, & Wingfield, 2010; Schmidtke, 2014; Wendt, Dau, & Hjortkjær, 2016; see Schmidtke, 2018, for a review), indicating that task‐external factors also affect pupillary responses during language comprehens...…”
Section: Introductionmentioning
confidence: 99%
“…Research examining the task‐evoked pupillary response (TEPR) provides evidence that the relationship between pitch accenting and referent status affects comprehenders' cognitive load during spoken discourse processing. Generally, smaller pupillary responses are observed when language processing is facilitated by intrinsic characteristics of the linguistic input such as speech quality (Koch & Janse, 2016; Kuchinsky et al, 2013; McGarrigle, Dawes, Stewart, Kuchinsky, & Munro, 2017; Tamási, McKean, Gafos, Fritzsche, & Höhle, 2017; Wagner, Toffanin, & Başkent, 2016; Winn, Edwards, & Litovsky, 2015; Zekveld, Kramer, & Festen, 2010), lexical characteristics (Chapman & Hallowell, 2015; Frank & Thompson, 2012; Geller, Landrigan, & Mirman, 2019; Geller, Still, & Morris, 2016; Guasch, Ferre, & Haro, 2017; Haro, Guasch, Vallès, & Ferré, 2017; Hyönä, Tommola, & Alaja, 1995; Kuchinke, Võ, Hofmann, & Jacobs, 2007; Ledoux et al, 2016; Lõo, van Rij, Järvikivi, & Baayen, 2016; Papesh & Goldinger, 2012), lack of syntactic ambiguity (Ben‐Nun, 1986; Just & Carpenter, 1993; Nikuni, Yasunaga, Iwasaki, & Muramoto, 2015; Sauppe, 2017; Schluroff, 1982; Sevilla, Maldonado, & Shalóm, 2014), and discursive implications (Demberg & Sayeed, 2016; Tromp, Hagoort, & Meyer, 2016). Conversely, larger pupillary responses are observed when language must be comprehended while simultaneously performing other tasks (Causse, Peysakhovich, & Fabre, 2016; Demberg & Sayeed, 2016; Koelewijn, de Kluiver, Shinn‐Cunningham, Zekveld, & Kramer, 2015; Koelewijn, Shinn‐Cunningham, Zekveld, & Kramer, 2014; Kramer et al, 2013) as well when language comprehension is difficult due to conditions such as aphasia and cognitive aging (Chapman & Hallowell, 2015; Hochmann & Papeo, 2014; Koch & Janse, 2016; Piquado, Isaacowitz, & Wingfield, 2010; Schmidtke, 2014; Wendt, Dau, & Hjortkjær, 2016; see Schmidtke, 2018, for a review), indicating that task‐external factors also affect pupillary responses during language comprehens...…”
Section: Introductionmentioning
confidence: 99%
“…In the first period, during the 400 ms that preceded the start of the trial, the baseline (BL) of pupil dilation of each participant was set, this being a measurement of pupil diameter. At the same time, the point of gaze fixation was determined [ 38 ]. After that, pupil dilation was considered during the time of presentation of the pseudoword (PW).…”
Section: Methodsmentioning
confidence: 99%
“…Kuchinke, Võ, Hofmann, and Jacobs (2007) showed that low-frequency words elicited a larger pupil response than high-frequency words, suggesting a processing advantage for regularly encountered words (also see Haro, Guasch, Vallès, & Ferré, 2016). Guasch, Ferré, and Haro (2016) showed that Spanish-Catalan bilinguals processed cognate words (translation equivalents that share a similar form) with greater ease than words that do not have a cognate in the other language. One recent lexical-decision study suggests that results from RT data and pupillometry can sometimes diverge.…”
Section: Pupillometry In Linguistic Researchmentioning
confidence: 99%